APLIKASI UJIAN SELEKSI MASUK MAHASISWA BARU : Studi Kasus : Kampus STMIK BANDUNG - Linda Apriyanti; Radityo Yoga Pratama; Siti Yuliyanti (LPPM STMIK BANDUNG, 2019)
The Entrance Selection Examination is a must for all agencies, because the instant wants to get people who are worthy to be part of the agency. With the entrance examination test, the candidates who have or have passed the minimum standard in conducting this selection test can be achieved. Especially if this selection exam is held in universities, in universities it is very important to take the entrance examination exam, because it can find highly competent prospective students. Examinations using written paper or conventional examinations have several disadvantages, such as adjusting test data with people who register for exams, how much they buy paper, and errors in correcting test answers from prospective students. In this study, an application has been developed which can be used to register new students and also conduct entrance examination tests to make it easier for institutions to record registrants and also for the selection of test examinations conducted. The system is named Selection of the Online Entrance Test for STMIK Bandung. In addition, the answers to the exam will be corrected by the system that has been made so as to reduce the risk of mistakes in correction that can harm prospective students and institutions. Designing with the waterfall method and system design using UML to simplify the design. In this system there is an automatic e-mail to provide information on the schedule of examinations and announcement of graduation in order to accelerate the process of receiving new students.